Macrotrichurus granzottorum, a new species of termitophilous rove beetle from Brazil (Staphylinidae: Aleocharinae: Termitonannini) - Silva, Ruan Felipe Da; Caron, Edilson; Moreno, Carlos (Zootaxa, 2025)
The genus Macrotrichurus Silvestri (Coleoptera: Staphylinidae: Aleocharinae: Termitonannini) is composed of two species that are associated with termite nests of the genera Anoplotermes Müller, Cornitermes Wasmann and Orthognathotermes Holmgren, from southeastern Brazil. In this paper, we describe Macrotrichurus granzottorum Da-Silva, Caron & Moreno sp. nov., from southwestern Brazil from nests of Patawatermes turricula (Silvestri), representing a novel host record for the genus. Additionally, we provide an updated taxonomic key for Macrotrichurus species, a revised diagnosis for the genus, notes on behavior, and discussion about hosts. This research extends the known distribution of the genus to the state of Mato Grosso do Sul.